Solution-processed high-performance p-channel copper tin sulfide thin-film transistors. Issue 29 (2nd July 2021) - Mude, Narendra Naik; Bukke, Ravindra Naik; Jang, Jin
Abstract : We introduce a solution-processed copper tin sulfide (CTS) thin film to realize high-performance of thin-film transistors (TFT) by optimizing the CTS precursor solution concentration. Abstract : We introduced solution-processed copper tin sulfide (CTS) thin films into thin-film transistors (TFTs) by varying the CTS precursor solution concentration. Systematic analysis of the optical and electrical properties of the CTS thin films was performed. Hall measurements confirmed the p-type conduction of CTS films with a hole mobility of 9.81 cm 2 V −1 s −1 . The successful integration of CTS thin films into the TFTs shows good switching properties such as a high mobility of 2.43 cm 2 V −1 s −1, a low subthreshold swing of 664 mV dec −1, a threshold voltage V TH of −0.53 V, and a hysteresis voltage of 2.31 V. Furthermore, the CTS TFT shows excellent stability under negative bias stress with a threshold voltage shift (Δ V TH ) of 0.54 V at a low operating voltage ( i.e., −5 V). The drain current of the CTS TFT shows an approximate 10% decrease over 2 days in air, indicating the need for a passivation layer to prevent the absorption of moisture. These results indicate the high performance of p-channel CTS TFTs at a low operating voltage and their integration in the development of low-power-consumption electronic devices.